Daily cycle of tropical kudzu leaf diffusive resistance, under low temperature - Netto, Adaucto Bellarmino de Pereira; Pinto, Hilton Silveira; Neto, Olinto Gomes da Rocha (Pesquisa Agropecuaria Brasileira, 1991)
Tropical kudzu Pueraria phaseoloides (Roxb.) Benth. has been widely used as a cover plant in rubber cultures of the major natural ruber-producing countries and in the Brazilian Amazon region. In this study, the effect of different levels of solar radiation (St) and low air temperature (Ta) on the daily leaf diffusive resistance cycle (Rf) was observed in plants of P. phaseoloides. Under reduced Ta and St, increased solar radiation induced Rf decrease, and an increase in Rf was also observed when St decreased at the end of the day. The vapour pressure deficit between the leaflet and the air (DPV) ranged from 1.0 to 2.4 mmHg. Under high St, Rf performed the same way as under low St, showing, however, an elevation in Rf around noon. DPV increased from 0.9 to 14.4 mmHg from 8:00 a .m. on.